"MOMENTUM MAYHEM" 3D PUZZLE GAME PROTOTYPE - Yerzhanuly, Azamat; Kabykesh, Dias; Ussoltsev, Vladimir; Serik, Yernar; Rysbek, Yelnaz (Nazarbayev University School of Engineering and Digital Sciences, 2024)
"Momentum Mayhem" is a 3D puzzle game prototype that aims to develop physics concepts in the game environment. The project comprises four stages: ideation, pre-production, production, and post-production. The ideation phase involved analyzing popular physics-based games such as "Fall Guys" and "We Were Here" to inspire unique gameplay concepts. In the pre-production phase, the team outlined the game's requirements and designed its architecture. The production phase focused on creating and integrating essential game components, including character controllers, environmental objects, UI/UX, level maps, and multiplayer functionality. "Momentum Mayhem" leverages Unity for its game engine and Photon PUN 2 for multiplayer networking. The game features physics-based puzzles requiring cooperative gameplay, aiming to enhance problem-solving skills and teamwork. This project highlights the growing game development scene in Kazakhstan by showcasing creative gameplay and technical skills. The document further elaborates on the background, related work, project approach, execution, and evaluation of the system.
Keywords: Type of access: Restricted; Game Design; Prototype; Unity; Multiplayer; Physics